2013
DOI: 10.1007/s12035-013-8562-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of S-Nitrosylated Protein Disulfide Isomerase on Mutant SOD1 Aggregation and Neuronal Cell Death in Amyotrophic Lateral Sclerosis

Abstract: Aggregation of misfolded protein and resultant intracellular inclusion body formation are common hallmarks of mutant superoxide dismutase (mSOD1)-linked familial amyotrophic lateral sclerosis (FALS) and have been associated with the selective neuronal death. Protein disulfide isomerase (PDI) represents a family of enzymatic chaperones that can fold nascent and aberrant proteins in the endoplasmic reticulum (ER) lumen. Recently, our group found that S-nitrosylated PDI could contribute to protein misfolding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 63 publications
2
60
0
Order By: Relevance
“…Despite thousands of SNO-proteins currently identified (ϳ3000), the observed specificity of S-nitrosylation in terms of target proteins and specific Cys residues is not entirely understood (81,82). S-nitrosylated proteins are implicated in the pathogenesis of various neurodegenerative diseases, including Alzheimer's, Parkinson's and Huntington's diseases, amyotrophic lateral sclerosis, Friedreich ataxia, and many others, where they influence the onset or development of neurodegeneration (8,23,(83)(84)(85).…”
Section: Discussionmentioning
confidence: 99%
“…Despite thousands of SNO-proteins currently identified (ϳ3000), the observed specificity of S-nitrosylation in terms of target proteins and specific Cys residues is not entirely understood (81,82). S-nitrosylated proteins are implicated in the pathogenesis of various neurodegenerative diseases, including Alzheimer's, Parkinson's and Huntington's diseases, amyotrophic lateral sclerosis, Friedreich ataxia, and many others, where they influence the onset or development of neurodegeneration (8,23,(83)(84)(85).…”
Section: Discussionmentioning
confidence: 99%
“…Cell models of AD pathology show that PDI inactivated through NO triggers an accumulation of poly-ubiquitinated proteins, an increase in ER stress, and induction of apoptosis (92,99). Similar reports using ALS and PD models show that overexpression prevents aggregation, whereas inhibition of PDI results in the accumulation of misfolded proteins (107,(116)(117)(118)(119). Further understanding of these metabolon, offering exciting new roles for these metabolic proteins as redox chaperones (Lee et al, unpublished observations).…”
Section: The Role Of Hbcat In Protein Folding and Redox-chaperone Actmentioning
confidence: 71%
“…We next investigated whether protein S-nitrosylation, a major posttranslational modifi cation by NO, might have a unique role in adipogenesis. Protein S-nitrosylation can occur even at low levels of NO and can affect the activity and stability of specifi c proteins (36)(37)(38)(39). Immunofl uorescence assay using an antibody against nitroso-cysteine showed that protein S-nitrosylation was higher in differentiated adipocytes (day 9) than in undifferentiated preadipocytes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Protein S-nitrosylation is a major reversible posttranslational modifi cation by NO that regulates protein function and stability (36)(37)(38)(39)(51)(52)(53)(54)(55)(56). Interestingly, it has been reported that protein S-nitrosylation is increased in adipose tissue in a model of obesity ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation